The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3928/01484834-20151110-06
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Patients' Satisfaction With Nursing Students' Care on a Perinatology Ward

Abstract: A high level of satisfaction with the care provided by nursing students indicates that the students were able to meet the patients' needs, which may serve as an indicator of the quality of nursing education and quality of care provided by future nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…This is consistent with patient satisfaction score in terms of this domain. However, in Oskay, Güngör, and Basgöl () and Can et al. () studies, patients were highly satisfied with the care they received from the nursing students (Can et al., ; Oskay et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with patient satisfaction score in terms of this domain. However, in Oskay, Güngör, and Basgöl () and Can et al. () studies, patients were highly satisfied with the care they received from the nursing students (Can et al., ; Oskay et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The first row in the project model ( Figure 2), in green, shows the theory that the nursing implementation of an evidence-based intervention (process) will have an affect on patient outcomes. Based on the findings from previous research, nursing students' involvement has a positive influence on patient care (Austria, Baraki and Doig, 2013;Marks & Koren, 2011;Oskay, Gungor & Basgol, 2015). Therefore, nursing students' implementation of evidence-based interventions will have positive impact on the quality of patient care and will result in improved patient outcomes.…”
Section: Project Model and Rationalementioning
confidence: 99%
“…Research has shown that the care patients receive from nursing students improves patient satisfaction (Oskay, Gungor & Basgol, 2015). Improved patient satisfaction will have a positive effect on patient care and lead to improved patient outcomes (Austria, Baraki & Doig, 2013;Marks & Koren, 2011;Oskay, Gungor & Basgol, 2015).…”
Section: Significance For Nursingmentioning
confidence: 99%
See 2 more Smart Citations